The mediating and moderating roles of entrepreneurship education in the perceived acquisition of entrepreneurial learning and knowledge - Frances Y. M. Chang; Muhammad Aftab Alam; Murray Taylor (Journal of Innovation & Knowledge (JIK), 2025)
Entrepreneurship education (EE) is a pivotal inspiration for students' efforts to acquire entrepreneurial knowledge (EK), which can enable them to found new business ventures. We draw on entrepreneurial inspiration theory to develop a framework that we use to test (a) the mediating effect of entrepreneurship education and (b) the moderating effects of different pedagogical approaches on the relationship between students' entrepreneurial intention (EI) and EK. The results reveal that entrepreneurship has significant and positive direct and indirect effects on the relationship between EI and EK. Importantly, our analyses reveal that the different pedagogical approaches used in business schools to impart EK have strong positive moderating effects in this context. An examination of these pedagogical approaches indicates that assessments can enhance university students' EK most significantly, followed by in-class activities and lectures. We discuss the results of this study and its implications for entrepreneurship educators and policymakers seeking to design effective curricula.
Keywords: A02; I02; 650; Entrepreneurial knowledge; Entrepreneurial inspiration; Entrepreneurial intention; Entrepreneurship education; Pedagogical approaches